LEGAL ANALYSIS OF UNLAWFUL ACTS RESULTING IN PATIENT PARALYSIS POST-CHIROPRACTIC THERAPY - Akbar Avatar Silas Putra; Abdullah Fikri (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
This study aims to analyze the legal aspects of unlawful acts causing paralysis in patients following chiropractic therapy. Chiropractic therapy, as a form of alternative medicine, has grown in popularity; however, serious complications such as paralysis require thorough examination of the therapist’s legal liability. This research employs normative and empirical approaches by reviewing health regulations and tort law principles. Data were gathered through literature review and interviews with victims and health law experts. The findings indicate that chiropractic practitioners must adhere to established standards and possess recognized expertise to avoid patient harm. If paralysis occurs due to negligence or procedural errors, practitioners may face legal sanctions based on unlawful acts, including compensation claims and criminal liability. The study recommends stricter supervision of chiropractic practices by relevant authorities to protect patients’ rights and prevent unlawful conduct. In conclusion, the legal analysis strengthens patient protection post-chiropractic therapy and clarifies the responsibility limits of the practitioners.